2001
DOI: 10.1038/sj.onc.1204889
|View full text |Cite
|
Sign up to set email alerts
|

Failure of hormone therapy in prostate cancer involves systematic restoration of androgen responsive genes and activation of rapamycin sensitive signaling

Abstract: Androgen deprivation therapy for advanced prostate cancer is often e ective, but not curative. Molecular pathways mediating the therapeutic response and those contributing to the subsequent hormone-refractory cell growth remain poorly understood. Here, cDNA microarray analysis of human CWR22 prostate cancer xenografts during the course of androgen deprivation therapy revealed distinct global gene expression pro®les in primary, regressing and recurrent tumors. Elucidation of the genes involved in the transition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
76
0
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 117 publications
(86 citation statements)
references
References 16 publications
9
76
0
1
Order By: Relevance
“…Like Akt, p70 S6 kinase activity was also increased in C4-2 cells compared with LNCaP cells. The mTOR inhibitor, rapamycin, which inhibits p70 S6 kinase phosphorylation, inhibited proliferation of the androgen-independent C4-2 cells, but not of the parental androgen-dependent line, suggesting that proliferation in C4-2 cells is mediated by p70 S6 kinase as shown by others (Mousses et al 2001). We hypothesize that AR regulates the cell cycle in LNCaP cells while in C4-2 cells androgen independence arises due to cell-cycle regulation by p70 S6 kinase rather than AR.…”
Section: Discussionsupporting
confidence: 54%
“…Like Akt, p70 S6 kinase activity was also increased in C4-2 cells compared with LNCaP cells. The mTOR inhibitor, rapamycin, which inhibits p70 S6 kinase phosphorylation, inhibited proliferation of the androgen-independent C4-2 cells, but not of the parental androgen-dependent line, suggesting that proliferation in C4-2 cells is mediated by p70 S6 kinase as shown by others (Mousses et al 2001). We hypothesize that AR regulates the cell cycle in LNCaP cells while in C4-2 cells androgen independence arises due to cell-cycle regulation by p70 S6 kinase rather than AR.…”
Section: Discussionsupporting
confidence: 54%
“…These results suggest that temporal changes do progress to significant and fixed change. A cDNA microarray analysis of human CWR22 prostate cancer xenografts during androgen deprivation therapy revealed temporal changes in the gene expression profile as a function of therapy response (Mousses et al, 2001). It was suggested that changes in the expression of genes involved in the transition between primary, regressing and recurrent tumors might point to molecular mechanisms that affect therapy failure and tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Western blot and antisense experiments demonstrated that CWR-R1 cells expressed moderate levels of PKCe and relied on this protein to survive in the presence of phorbol esters, while the apoptosis normally induced by phorbol esters in PKCe-deficient LNCaP cells was dependent on the presence of Bax. Forced expression of PKCe in LNCaP cells was sufficient to confer a significant resistance to phorbol esters and this resistance was associated with an inhibition ofIntroduction Prostatic epithelial cells that survive androgen deprivation therapy engage multiple molecular pathways to escape their normal apoptotic fate, to restore the expression of androgen-responsive genes, and to disrupt the growth-restraining activity of the retinoblastoma (Rb) family of transcriptional represser proteins (Gregory et al, 1998;Fribourg et al, 2000;Mousses et al, 2001). The present study has focused on the first of these hallmarks of advanced carcinoma of the prostate (CaP), because defects in the apoptotic machinery are likely to be an important contributing factor in the resistance of some CaP cells to chemotherapy or irradiation and to the recurrence of CaP after androgen deprivation.…”
mentioning
confidence: 99%